2011
DOI: 10.1063/1.3651763
|View full text |Cite
|
Sign up to set email alerts
|

Fragility of iron-based glasses

Abstract: The electronic structure origin for ultrahigh glass-forming ability of the FeCoCrMoCBY alloy system J. Appl. Phys. 110, 033720 (2011) Enhancement of glass-forming ability and corrosion resistance of Zr-based Zr-Ni-Al bulk metallic glasses with minor addition of Nb J. Appl. Phys. 110, 023513 (2011) Structural origin underlying poor glass forming ability of Al metallic glass J. Appl. Phys. 110, 013519 (2011) Interatomic potential to calculate the driving force, optimized composition, and atomic structure o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Na et al [47] studied the fragility of Fe-based glasses, and found that m and glass formability are inversely correlated for Fe-based alloys. This suggests that the amorphous phase in Fe-based alloys is kinetically stabilized.…”
Section: Mechanism Of Grain Refinement By Uramentioning
confidence: 99%
“…Na et al [47] studied the fragility of Fe-based glasses, and found that m and glass formability are inversely correlated for Fe-based alloys. This suggests that the amorphous phase in Fe-based alloys is kinetically stabilized.…”
Section: Mechanism Of Grain Refinement By Uramentioning
confidence: 99%
“…Although the small interfacial energy is not beneficial for the GFA, the formation of ISRO is expected to increases the melt viscosity [40,41]. Sluggish atomic movements due to a high viscosity affect the nucleation and growth rate and may lead to an increasing GFA as demonstrated by Na et al for Fe-based bulk glass-forming liquids [42]. The importance of the viscosity for the glass formation in this system is supported by the observation that the viscosity at the liquidus temperature of the Ti 60 Zr 15 Cu 17 S 8 bulk glass-forming alloy composition (same alloy family as Ti 58 Zr 7.5 Ni 18.5 Cu 12 S 4 ) is approximately one order of magnitude higher than that of the Ti 37 Zr 42 Ni 21 liquid [22,30].…”
Section: Discussionmentioning
confidence: 99%